Analysis of the mineral composition of hypomineralized first permanent molars - Martinović, Brankica T; Ivanović, Mirjana; Milosavljević, Zoraida; Mladenović, Raša (Vojnosanitetski pregled, 2015)
Background/Aim. Hypomineralization of molars and incisors (molar-incisor hypomineralization – MIH) is defined as enamel hypomineralization of systemic origin of one or more of the four first permanent molars, which may be associated with changes in the maxillary, and less frequently in the permanent mandibular incisors. The aim of this study was to investigate the mineral content in hypomineralized teeth as a contribution to under-standing the origin of these changes, which will be important for effective restorative approach. Methods. A total of 10 extracted first permanent molars diagnosed with MIH were used in the study as the experimental group, and intact first premolars extracted for orthodontic reasons were used as the control group. A certain surface of hypomineralized аnd healthy enamel and dentin was analyzed using a scanning electron microscope equipped with an energy-dispersive spectrometer (SEM/EDS). Results. By conducting quantitative chemical analysis of the distribution of the basic chemical elements, it was found that the concentration of calcium (Ca) and phosphorus (P) was significantly higher in healthy enamel (Ca = 28.80 wt%, and P = 15.05 wt%) compared to hypomineralized enamel (Ca = 27.60 wt% and P = 14.32 wt%). Carbon (C) concentration was statistically significantly higher in hypomineralized enamel (C = 11.70 wt%) compared to healthy enamel (C = 10.94 wt%). Hypomineralized and healthy enamel did not differ significantly regarding the ratio of calcium and phosphorus concentrations whereas the ratio of calcium and carbon concentrations was statistically significantly higher in healthy enamel compared to hypomineralized enamel. Conclusion. Concentration of the main chemical elements, primarily calcium and phosphorus, is significantly reduced in hypomineralized enamel whereas carbon concentration is increased compared to healthy enamel.
Keywords: tooth demineralization; molar; dental enamel; dentin; elements; microscopy; electron; scanning